2001
DOI: 10.1111/j.1600-0463.2001.tb05819.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in semen quality in Europe

Abstract: Recent reports have indicated a decrease in semen quality of men in some countries, and suggested regional differences. A study was undertaken of semen samples from 1082 fertile men from four European cities (Copenhagen, Denmark; Paris, France; Edinburgh, Scotland; and Turku, Finland). Semen analysis was standardized, inter‐ laboratory differences in assessment of sperm concentration were evaluated, and morphology assessment centralized. Lowest sperm concentrations and total counts were detected for Danish men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
111
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(129 citation statements)
references
References 35 publications
10
111
2
6
Order By: Relevance
“…49 It is important to emphasize the marked geographical differences in the last secular trend in male reproductive function. [50][51][52] The explanation for this regional trend is not known. Giwercman and LundgergGiwercman 46 argue that the population may genetically differ, but that probably environmental or life style related factors are operating.…”
Section: Contribution Of Environmental Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…49 It is important to emphasize the marked geographical differences in the last secular trend in male reproductive function. [50][51][52] The explanation for this regional trend is not known. Giwercman and LundgergGiwercman 46 argue that the population may genetically differ, but that probably environmental or life style related factors are operating.…”
Section: Contribution Of Environmental Factorsmentioning
confidence: 98%
“…Nevertheless, the observed discrepancies between studies suggest regional differences in semen quality. [20][21][22] Variations in environmental factors, industrial pollution and/or lifestyle could explain these discrepancies. A large number of environmental factors can pollute air, drinking water and food.…”
mentioning
confidence: 99%
“…These questions prompted an unprecedented, prospective and coordinated action in Finland, Denmark, Scotland and France in which sperm parameters were related to couple fecundity-almost 1000 couples took part. [42][43][44] The results of the combined data of the four countries demonstrated an overall trend of a relation between increasing sperm concentrations up to about 50 million per ml with shorter times to pregnancy corresponding with better fecundity. However, the results also revealed that the relation between sperm concentration and couple fecundity was far from straightforward.…”
Section: Reproduction Fecundity and Fertility: What Is Their Relatiomentioning
confidence: 94%
“…Previous data from screened and general populations showed that there are obvious differences in semen quality between continents [6], countries [7] and even different areas in the same country [6,8,9]. Some of the studies also revealed temporal differences [10].…”
Section: Dear Editormentioning
confidence: 99%
“…Profound comments on this regard have been made and published in the Special Issue in Asian Journal of Andrology on "Semen analysis in 21st Century Medicine" in Issue 1 in 2010 [2][3][4][5]. In this letter, I would like to present some of my views and suggestions on reference limits of semen parameters.Previous data from screened and general populations showed that there are obvious differences in semen quality between continents [6], countries [7] and even different areas in the same country [6,8,9]. Some of the studies also revealed temporal differences [10].…”
mentioning
confidence: 99%